2007
DOI: 10.1590/s0102-09352007000600009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de dois sensores portáteis para mensuração da glicemia em cães

Abstract: Avaliou-se a precisão analítica e clínica de dois sensores portáteis para mensuração da glicemia em cães. Os valores da mensuração da glicemia obtidos com os sensores foram comparados com aqueles obtidos pelo método padrão da glicose oxidase, por meio da análise de correlação e da análise da grade de erros. Os resultados gerados pelos sensores não foram diferentes do método padrão. Conclui-se que ambos os sensores são adequados para mensuração da glicemia em cães.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
1
11
0
7
Order By: Relevance
“…Many studies have been published where these “human” devices have been tested in dogs and other animals, and at the time this study was performed, the previous study in dogs had been published in 2009 and new PBGM had been developed and become available since then. In published studies, not all PBGM were accurate enough to be used in dogs and even those specifically developed for animals led to inappropriate clinical interpretation …”
mentioning
confidence: 99%
“…Many studies have been published where these “human” devices have been tested in dogs and other animals, and at the time this study was performed, the previous study in dogs had been published in 2009 and new PBGM had been developed and become available since then. In published studies, not all PBGM were accurate enough to be used in dogs and even those specifically developed for animals led to inappropriate clinical interpretation …”
mentioning
confidence: 99%
“…However, the mean haematocrit values (±standard deviations) found in T 0 to T 4 , in the present study were 35.20±5.28 %; 45.74± 3.83 %; 46.07±6.81 %; 43.02±6.07 %, and 38.21±3.81 %, respectively, revealing that none of the values were outside the range established by the referred to authors. Bluwol et al (2007) demonstrated that the determination of glucose in total blood from portable devices were effective in dogs. Moreover, Aleixo et al (2006) suggested a repeat blood glucose test in dogs, in order to verify the accuracy of the result, since factors such as haematocrit, dehydration, and sample size might change it.…”
Section: Resultsmentioning
confidence: 99%
“…The laboratory determination of glucose, lactate, triglycerides, and blood cholesterol involves enzymatic, colorimetric, and/or photometric spectrum methods (Bruss and Lipids and ketones 2008;Kaneko 2008;Stockham and Scott 2008). The practicality of portable devices for this type of measurement enabled these to be widely used not only in human medicine but also in veterinary medicine; as for the latter, it is important to prove its efficacy in animals, which has been done by several authors (Franchini et al 2004;Aleixo et al 2006;Bluwol et al 2007;Santos et al 2008). Although, Teixeira-Neto et al (2011) tested the measurements of glucose, lactate, triglycerides, and cholesterol through the portable device Accutrend® Plus and concluded that the same was ineffective in the equine clinic, these authors developed the study with a group of horses at rest.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4) Deste modo, é fundamental que os aparelhos adotados sejam confiáveis, principalmente para avaliarem amostras coletadas de pacientes em diferentes graus de comprometimento da integridade metabólica e de saúde geral. (4)(5)(6) O mercado tem oferecido GT desenvolvidos para uso exclusivo na assistência veterinária. É esperado que tais aparelhos sejam programados para processarem amostras capilares das espécies domésticas a que se propõe, incluindo as possíveis variações hematológicas.…”
Section: Introductionunclassified